Impact of Tourniquet Type on Outcomes in ORIF of Pediatric Distal Radius Fractures - Jacopo Conteduca; Damiano Longo; Alberto Casto; Giorgio Giannini; Luigi Meccariello; Igor Rausa; Giuseppe Rollo (Medicinski glasnik, 2025)
Purpose: The objective of this study was to assess the benefits of utilizing a silicone ring tourniquet in relation to traditional pneumatic cuff tourniquets and scenarios without any tourniquet intervention. The tested hypothesis was that the clinical results could be increased after use of the silicone ring tourniquet. Methods: The study was monocentric and retrospective evaluation of collected data. Inclusion criterion was open reduction and internal fixation of a displaced distal radius fracture in pediatric population (6-12 years). The pneumatic tourniquet (PT) group involved 18 patients, the no tourniquet (NT) 19 patients and the silicon ring (SR) group 19 patients. All patients were followed for 6 months. Primary criterion was the VAS score at 1 day and 7 days postop. Secondary criteria were delay of discharge, time of surgery and occurrence of complications. Results: The VAS score in the first and seven day postop was respectively 3.8 ±1 and 2.0 ± 0.5 for the PT group, 3.5 ± 0.5 and 1.8 ± 0.2 for the NT group and 3.2 ± 0.8 and 1.8 ± 0.4 for the SR group without statistically significant differences (p>0.1). There was a non-significant higher rate of complication PT group, especially for skin complications and a higher time of surgery in the NT group. Conclusions: The proposed hypothesis was not validated, as there were no notable changes observed in the clinical outcomes. Additionally, the analysis of complications revealed no evidence of bias. However, the reduced incidence of skin complications may indicate a beneficial effect associated with the silicone ring tourniquet.
Keywords: clinical outcomes; guidelines; pediatric; tourniquet